EFFECT OF SCANDIUM ON HIDROGEN DISSOCIATION ENERGY AT MAGNESIUM SURFACE: AB INITIO DFT STUDY - I Wayan Sutapa; Ria Armunanto; Karna Wijaya (Indonesian Journal of Chemistry, 2010)
The dissociative chemisorption of hydrogen on both pure and Sc-incorporated Mg(0001) surfaces have been studied by ab initio density functional theory (DFT) calculation. The calculated dissociation energy of hydrogen molecule on a pure Mg(0001) surface (1.200 eV) is in good agreement with comparable theoretical studies. For the Sc-incorporated Mg(0001) surface, the activated barrier decreases to 0.780 eV due to the strong interaction between the molecular orbital of hydrogen and the d metal state of Sc. This could explain the experimentally observed improvement in absorption kinetics of hydrogen when transition metals have been introduced into the magnesium materials.